KAJIAN KOMPETENSI DAN PROFESIONALISASI GURU - Ananda, Lala Jelita (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2017)
This research was executed at SMK Sandhy Putra 2 Medan. The purpose of this research is to know how far the teachers understanding of the competence of educators. Researchers use interviews and questionnaires to know the competence of professional teachers. Based on calculations, it is shown that the mean value of teacher competence data is 180.7. With the lowest 168 andÂ  the highest 195 so that the range of data is 27. Median data 182, the Modus is 182 and the standard deviation 8.0006. Based on these results concluded that the teacher still does not know what the legal basis of the implementation of education and essenceÂ Key Words: Competence, Profesional, Teacher